The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1017/s004393391800003x
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of avian intestinal ion transport

Abstract: Summary The gut has great importance for the commercial success of poultry production. Numerous ion transporters, exchangers, and channels are present on both the apical and the basolateral membrane of intestinal epithelial cells, and their differential expression along the crypt-villus axis within the various intestinal segments ensures efficient intestinal absorption and effective barrier function. Recent studies have shown that intensive production systems, microbial exposure, and nutritional management sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…SGLT1 is a co-transporter of glucose and sodium. Concurrent absorption of glucose and sodium establishes a gradient that facilitates the movement of sodium and water through the paracellular space [29]. This might be helpful in reducing diarrhea, which is a common symptom during enteric diseases, thus alleviating its negative impacts on the bird.…”
Section: Discussionmentioning
confidence: 99%
“…SGLT1 is a co-transporter of glucose and sodium. Concurrent absorption of glucose and sodium establishes a gradient that facilitates the movement of sodium and water through the paracellular space [29]. This might be helpful in reducing diarrhea, which is a common symptom during enteric diseases, thus alleviating its negative impacts on the bird.…”
Section: Discussionmentioning
confidence: 99%
“…The penetration of the proboscis of P. constrictum in the muscularis and the aforementioned damage could alter the homeostasis in the host. It has been shown that the isotonicity of luminal contents in the presence of structural damage on the mucosa is difficult to maintain, because intestinal epithelium promotes the strong exchange of water and electrolytes with the body's extracellular fluids (Nighot & Nighot, 2018). In addition, enterocyte alteration can cause intestinal secretion – reabsorption function can quickly promote severe body fluid depletion and affect the absorption of salts by channels (Nighot & Nighot, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The high number of parasites severely infecting the hosts may cause malabsorption of nutrients by the host as a result of mucosal reduction due to the host–parasite nutritional competition (Bush et al ., 2001). Similarly, the increased damages in the intestinal tissue due to a higher number of parasites could alter the homeostasis in the host (Nighot & Nighot, 2018). We are not aware of any report of similar damages.…”
Section: Resultsmentioning
confidence: 99%